The Relationship Between Voluntary Disclosure, Accounting Earnings Quality, and Its Impact on Investor Confidence: An Applied Study at the Middle East Investment Bank for the Period 2010–2024 - Batool Hadi Mohammed; Saifuldeen Jabbar Ghulam; Fawziya Jassoom Kadhim (International Journal on Economics, Finance and Sustainable Development, 2026)
The paper employs an applied case study of the Middle East Investment Bank to investigate the relationship between voluntary disclosure, accounting profits quality, and investor confidence from 2010 to 2024. The research problem stems from the following question: To what extent does optional disclosure enhance earnings quality, and how will it affect investor confidence? This study incorporates quantitative tools for measuring earnings quality (i.e., accrual models) and disclosure content analysis along with market indicators of investor confidence, and uses a descriptive-analytical methodology based on reviewing financial reports and voluntary disclosures issued by the bank. To determine these relationships among the variables, multiple linear regression tests were performed along with mediation relationship tests. Findings from this preliminary research indicate that a higher level of earnings quality due to optional disclosure is likely to increase investor confidence, while one key mediating factor in the relationship between investor confidence and voluntary disclosure is earnings quality. The findings also suggest that if bank management wants to improve financial data reliability, investor confidence, and the stability of financial markets, it should make more voluminous voluntary disclosures and engage in more transparent accounting practices.